Legislative correlates of the size and number of protected areas in Canadian jurisdictions. (November 2015) - Leroux, Shawn J.; Brimacombe, Chris; Khair, Shahira; Benidickson, Jamie; Findlay, C. Scott
Abstract: Protected area legislation provides the statutory authority for the establishment and management of protected areas. Yet few studies have investigated the relationship between protected area legislation and those attributes of protected areas that are likely to affect their success in achieving biodiversity conservation objectives. Here we investigate the association between the size and number of protected areas within Canadian provincial, territorial and federal jurisdictions and provisions of the corresponding legislation using a Before–After/Control–Impact design. We found that jurisdictions with legislation that includes explicit provisions for donations in cash or in-kind and many types of stakeholder involvement had, on average, larger (1.01 × to 29.0 ×) protected areas after versus before legislation enactment, compared to those without such provisions. Jurisdictions with legislation that includes provisions for protected area co-management with local or aboriginal/indigenous communities also had, on average, a higher rate of park establishment after (0.17–23.7 protected areas/year) versus before (0.17–6.34 protected areas/year) legislation enactment, compared to those without such provisions (0.09–5.00 protected areas/year; 0.21–5.30 protected areas/year after and before respectively). Similar patterns were detected for jurisdictions with legislation that includes provisions for operating and/or capital cost recovery. Our results suggest that legislative provisions that facilitate stakeholder participation and cost recovery may contribute to the establishment of more and larger protected areas. As signatories to the Convention on Biological Diversity attempt to expand protected area networks, they should consider including provisions concerning stakeholder involvement and cost recovery into protected areas legislation. Highlights: We study how protected area legislation influences the traits of protected areas. We conducted a case study of Canadian provinces, territories and National parks. Jurisdictions with legislated stakeholder involvement had larger protected areas. Jurisdictions with legislated stakeholder involvement had more protected areas. Our results suggest that a good legal process may lead to conservation benefits.